(untitled) (Veterinary Science, 2017)
The electro analgesic technique through reflex action (EMAR) is simple and not aggressive at all, nevertheless few studies have been done to standardize the results. In the present study, different parameters were evaluated in order to compare the results with the traditional use of acetate of methyl prednisolone. The clinic model was done in 10 polo horses, between 2-3 years old, through radiographic studies of the tarsus-crural joint with observed signs of osteochondrosis, therefore the plan was to correlate the radiographic images with the clinic evaluation. The animals were subjected to hard exercise in order to perceive the sign of effusion and limp. The horses were divided in two groups of five animals each; group1 received 40 mg of methyl prednisolone in the joint and group2 received two dairy treatment of EMAR during 8 days. The electro stimulation effect was provoked by SEAKIT equipment and the clinical examination was done every day posttreatment in both groups considering: a) effusion grade, b) post training limp and c) tarsus forces flexion. The statistical method used was Kruscal Wallis for the variables a) and b), and with chi2 for variable c). It was observed a significant (p0.01) clinical improvement through the EMAR technique in the variable a) and b) with respect to those animals treated with methyl prednisolone. The EMAR treated horses did not showed pain at tarsus forces flexion until 9 days post treatment, showing significant improvement with respect to those horses treated with methyl prednisolone (p0,05). Under the present trail condition, it was concluded that the EMAR treatment was better than the acetylmethyl prednisolone group in the degenerative joint pathology.